2021
DOI: 10.1080/14767058.2021.1888924
|View full text |Cite
|
Sign up to set email alerts
|

Screening for late preeclampsia at 35–37 weeks by the urinary Congo-red dot paper test

Abstract: Background: Several cross-sectional studies have investigated the incidence of urinary Congored dye positivity in women with preeclampsia (PE), compared to unaffected pregnancies, and reported very high sensitivity and low false positive rate in the diagnosis of PE. Objective: To determine the performance of the urinary Congo-red dot paper test at 35-37 weeks' gestation in the prediction of delivery with PE at 2 and >2 weeks after assessment. Methods: This was a prospective observational study in women attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Our findings showed that CRDPT is not effective in the diagnosis of HDP (Figure 2). Our findings are in support of Dorbert et al, who reported that the performance of CRDPT in diagnosing PE is poor (27). Furthermore, a study by McCarthy et al that evaluated urinary congophilia levels in women with PE, chronic kidney disease without PE, and lupus nephritis in non-pregnant women, confirmed that the CRDPT cannot differentiate between these conditions, suggesting that CRDPT is not a reliable tool in the prediction of PE or HDP (26).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings showed that CRDPT is not effective in the diagnosis of HDP (Figure 2). Our findings are in support of Dorbert et al, who reported that the performance of CRDPT in diagnosing PE is poor (27). Furthermore, a study by McCarthy et al that evaluated urinary congophilia levels in women with PE, chronic kidney disease without PE, and lupus nephritis in non-pregnant women, confirmed that the CRDPT cannot differentiate between these conditions, suggesting that CRDPT is not a reliable tool in the prediction of PE or HDP (26).…”
Section: Discussionsupporting
confidence: 88%
“…These findings designate the variance in pathology of the two classes of PE (26). In contradiction to results reported thus far, Dobert et al reported that the CRDPT results were "poor" in women between 35 and 37 weeks of gestation (27).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations